Pendekatan CRT (Culturally Responsive Teaching) dalam Pembelajaran Kalam - Sulaeman, Islamiyah (Prosiding Konferensi Nasional Bahasa Arab, 2023)
This research aimed to describe the concept of the Culturally Responsive Teaching (CRT)approach and its implementation in teaching Arabic Speaking. The research method used was aliterature review with data collection techniques such as editing, organizing, founding, and dataanalysis techniques by Miles and Huberman. The research findings indicated that theimplementation of CRT has the potential to create a more inclusive, relevant, and supportivelearning environment. Teachers who integrated students' cultural elements into the content,facilitated students' knowledge construction, reduced prejudice in differences, promoted socialjustice, and fostered students' academic development could create a more positive learningexperience. The results of this research can serve as a reference that can be widely adopted inlanguage teaching to promote respect for differences and encourage inclusion in education.